(x^a)(x^b)=x^(a+b)
(ab)(cd)=(a)(b)(c)(d)
x^-m=1/(x^m)
(3y^-4)(2y^-4)=
(3)(y^-4)(2)(y^-4)=
(6)(y^-8)=
6/(y^8)
Use the formula
S=wh+lw+ls+lp
And you should get your answer.
1.)label the shape with length width side and p then multiply the letters that are together in the formula.then add whatever you got when you multiples tougher and that's ur answer
Hi there!
To find an equivalent function for this function, we can just simplify it.
f(x) = (6)4x
f(x) = 24x
is an equivalent function.
Hope this helps!
Answer:
9 square units
Step-by-step explanation:
1/2(3)=1.5
1/2(6)=3
2
1/2(3)=1.5
1/2(2)=1
1.5+1.5+3+2+1=9